A Proper Lubricant for a Swage Process in a Hard Disk Drive Factory Determined by Explicit Dynamics Analysis - Watchara Bubpatha; Sorathorn Pattanapichai; Jatuporn Thongsri (My University, 2023)
Since the hard disk drive industries continue to be highly competitive, many factories aim to reduce waste costs by developing their manufacturing process. This article presents the swage process (SP) development to join components: the head gimbal assembly with an actuator arm by explicit dynamics analysis (EDA). First, EDA was employed to determine the total deformation ($\delta$) and equivalent (von Mises) stress ($\sigma$) after joining both components in the SP using a traditional lubricant currently used in the factory calculated by the friction coefficients. Then, the EDA results for the traditional lubricant were compared with the experimental results, and an agreement between both results was observed, confirming the EDA's credibility. Next, two additional different lubricants, including a non-lubricant as a control case, were investigated using the EDA. Finally, after comparing the EDA results for all four lubricants, the EDA results showed the proper type of lubricant, which can reduce the $\delta$ by 16.40% and $\sigma$ by 9.40% compared to the traditional lubricant. Accordingly, the research findings were applied as important information for determining the best lubricant for other HDD generations to suit the SP, which can reduce waste costs from the trial and error method.
Keywords: Hydraulic and Pneumatic Systems; Fuel Cells and Related Materials; Advanced Data Processing Techniques